Equations of normal
asked Nov 10, 2016 in Calculus Answers by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

Best answer

(1) If y=(2x-1)/(1-x), y=(2x-1)(1-x)^-1, y'=2(1-x)^-1+(2x-1)(1-x)^-2=



This is the slope of the tangent. The slope of the normal is -(1-x)^2=-1 when x=2.

Therefore the equation of the normal is y=-x+c where c is to be found by substitution of the coords when x=2.

At x=2, y=-3. Therefore -3=-2+c, c=-1. The equation of the normal is y=-x-1.

(2) P is found by solving -x-1=(2x-1)/(1-x); -(1+x)(1-x)=2x-1; x^2-1=2x-1, x^2-2x=0, x(x-2)=0 so x=0 or 2. We already know that x=2 is at the normal, so x=0 is the x-coord of P and the y-coord is -1, P(0,-1).

(3) y'=1/(1-x)^2 is the tangent. When x=0, y'=1 so the equation of the tangent is y=x+c and 0=-1+c, so c=1 and the equation of the tangent is y=x+1.


answered Nov 11, 2016 by Rod Top Rated User (486,900 points)
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
79,816 questions
83,633 answers
66,552 users